ANALISIS KINERJA KEUANGAN BANK BUMN DI INDONESIA PERIODE 2019 - 2021 - Rizky Poetri Audyta Sari, (2022)
This final project focuses on finding out how to describe the financial performance of liquidity, solvency and profitability in state-owned banks. Data retrieval uses the documentation method in the form of an annual report in the form of a ratio of BUMN Bank with LDR, CAR, and ROA proxies on the Indonesia Stock Exchange for the 2019 - 2020 period. BUMN as a source of national income with state assets. The amount of competition between banks and the financial technology industry builds competition between banks in intense competition, which affects the decline in interest loans. The analytical method used for this writing uses the trend analysis method. The results of the analysis of the financial performance of state-owned banks that the biggest trend is in the liquidity ratio experienced by BTN, the effect of income from securities, other positive trends experienced by BNI on the solvency ratio, the effect of increasing credit expansion and a positive trend on the profitability ratio experienced by BTN. With the definition that each bank has a relatively different quality and evaluation of capital according to the characteristics and management carried out by each bank.